Analýza fotbalového klubu Břeclav - Kubát, Lukáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Bakalářská práce se věnuje analýze fotbalového klubu MSK Břeclav. Práce je rozdělena na několik částí. První část uvádí teoretická východiska, v další části pak analyzuji klub pomocí SLEPT a SWOT analýzy. Na základě analýz a zjištěných údajů, pak podám návrhy řešení a jejich přínosy pro klub.

This bachlerors thesis deals with the analysis of the football club MSK Breclav. The work is divided into several parts. The first part presents the theoretical background,in the next section club will be analyzed with the SLEPT and SWOT analysis. Based on analysis of collected data solutions and suggestions will be proposed.
Analysis of the Football Club Břeclav
Keywords: Fotbal; sportovní klub; optimalizace; analýza SLEPT; analýza SWOT; financování; Football; Sports Club; optimization; SLEPT analysis; SWOT analysis; financing